Zooming-in for climate action: hyperlocal greenhouse gas data for mitigation action? - Jungmann, Maximilian; Vardag, Sanam Noreen; Kutzner, Florian; Keppler, Frank; Schmidt, Martina; Aeschbach, Nicole; Gerhard, Ulrike; Zipf, Alexander; Lautenbach, Sven; Siegmund, Alexander; Goeschl, Timo; Butz, André (Climate action, 2022)
While the international community has made progress in adopting goals and agreements in the field of climate change mitigation, efforts to reduce greenhouse gas (GHG) emissions are significantly lacking behind global ambitions for acceptable climate change. In this perspective, we discuss whether a window of opportunity for more effective climate action is emerging due to the convergence of new scientific and technological opportunities to provide high-resolution information on GHG emissions and emerging polycentric governance forms. We hypothesize that scientific and technological developments in the geophysical sciences and geoinformatics could provide the information policy makers need to put in place effective policies on climate change mitigation and to have measures to verify the effectiveness of their mitigation policies. To contribute to a better understanding of these developments and the requirements for effective climate action, new forms of inter- and transdisciplinary research become urgently necessary.